Effect of Sn content on strain hardening behavior of as-extruded Mg-Sn alloys - Zhao, Chaoyue; Chen, Xianhua; Pan, Fusheng; Gao, Shangyu; Zhao, Di; Liu, Xiaofang (Materials science & engineering. A, Structural materials : properties, microstructure and processing, 2018)
The effects of Sn content on strain hardening behavior of as-extruded Mg-xSn (x = 1.3, 2.4, 3.6 and 4.7wt%) binary alloys were investigated by uniaxial tensile tests at room temperature. Strain hardening rate, strain hardening exponent and hardening capacity were obtained from the true plastic stress-strain curves. After hot extrusion, the as-extruded Mg-Sn alloys are mainly composed of α-Mg matrix and second phase Mg2Sn, which only exists in Mg-3Sn and Mg-4Sn. Average grain size decreases from 15.6μm to 3.6µm with Sn content increases from 1.3 to 4.7wt%. The experimental results show that Sn content decreases strain hardening ability of as-extruded Mg-Sn alloys, but gives rise to an obvious elevation in tensile strength, yield strength and elongation of them. With increasing Sn content, strain hardening rate decreases from 3527MPa to 1211MPa at (σ-σ0.2) = 50MPa, strain hardening exponent decreases from 0.21 to 0.13 and hardening capacity decreases from 1.66 to 0.63. The variation in strain hardening behavior of Mg-Sn alloys with Sn content is discussed in terms of the influences of grain size and distribution of grain orientation.